2006
DOI: 10.1063/1.2192579
|View full text |Cite
|
Sign up to set email alerts
|

Sn O 2 nanoparticles in silica: Nanosized tools for femtosecond-laser machining of refractive index patterns

Abstract: We show that SnO 2 nanoclusters in silica interact with ultrashort infrared laser pulses focused inside the material generating a hydrostatic compression and photoelastic response of the surrounding glass. This effect, together with the laser-induced nanocluster amorphization, gives rise to positive or negative refractive-index changes, up to 10 −2 , depending on the beam-power density. This result points out a wide tuning of the refractive index patterns obtainable in silica-based optical technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…We underlined that the proposed synthesis method is not limited to the production of NS films on silicon substrates, but is instead applicable to other thermally stable substrates such as quartz for producing transparent functional films on transparent media that can be further processed into waveguides or other optical patterns, thanks to the photorefractive response of the NS material 46 Oxide nanocrystals (Methods and Supplementary Fig. S4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We underlined that the proposed synthesis method is not limited to the production of NS films on silicon substrates, but is instead applicable to other thermally stable substrates such as quartz for producing transparent functional films on transparent media that can be further processed into waveguides or other optical patterns, thanks to the photorefractive response of the NS material 46 Oxide nanocrystals (Methods and Supplementary Fig. S4).…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the strongly localized energy release, partial amorphization of the nanophase takes place in the glass 28 , accompanied in some cases by local compaction of the surrounding host 46 . Nanophase amorphization and host compaction are concomitant mechanisms (tunable by changing the laser power density) that may be used to induce local permanent modification of the refractive index up to approximately ± 10 − 2 , either positive or negative depending on the process parameters 46 . Importantly, this type of top-down processing is entirely implementable to the proposed bottom-up strategy of material synthesis, thus allowing for the design of a wide class of optoelectronic devices.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chiodini et al [25,26] reported unpatterned permanent changes in the refractive index of tin-silicate glass ceramic exposed to UV radiation. Paleari et al [27] reported refractive index patterning in a tin-silicate glass ceramic using an 800 nm femtosecond laser.…”
Section: Introductionmentioning
confidence: 99%